2017
DOI: 10.1177/0884533617719671
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Injectable Emulsion Survey With Gap Analysis

Abstract: These findings demonstrate the need for ongoing dissemination and education on standardized safe practices for ILE use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 18 publications
(59 citation statements)
references
References 41 publications
(55 reference statements)
2
53
0
Order By: Relevance
“…The American Society for Parenteral and Enteral Nutrition (ASPEN) published the results of a national survey on ILE use with a gap analysis . The results indicated that a majority in the United States still provide compounded PN to meet their patients’ needs.…”
Section: Ile Preparationmentioning
confidence: 99%
See 4 more Smart Citations
“…The American Society for Parenteral and Enteral Nutrition (ASPEN) published the results of a national survey on ILE use with a gap analysis . The results indicated that a majority in the United States still provide compounded PN to meet their patients’ needs.…”
Section: Ile Preparationmentioning
confidence: 99%
“…It was of great interest to note that only 5 or fewer PN admixtures were prepared by those institutions caring for 50% of adults, 82% of pediatrics, and 64% of neonates . Of the 16% minority using commercial MCB PN products in the United States, nearly 5% add separate ILEs to their 2‐chambered PN . Three‐chambered PN commercial products contain 3 macronutrients, each in a separate compartment, with or without electrolytes; vitamins and trace elements are added extemporaneously to the bag when prepared for the patient.…”
Section: Ile Preparationmentioning
confidence: 99%
See 3 more Smart Citations